IMPLEMENTASI STRATEGI KEBIJAKAN PELAYANAN KESEHATAN REPRODUKSI REMAJA DI KABUPATEN SEMARANG - Herni Afriyanti; Ari Subowo (Journal of Public Policy and Management Review, 2017)
The multilateral development scheme incorporates SRHR (Sexual and Reproductive Health and Rights) into the SDG'S (Suistanable Development Goals) indicator, it means that in all development aspects should not override the SRHR issues. Reproductive health services for teenagers have got no serious attention yet, whereas teenagers are the most vulnerable group that sustaining various risks of reproductive health problems. Major issues related to adolescent reproductive health also called by term Triad KRR (sexuality, HIV / AIDS and drugs) are actual issues that require the attention of all parties. This study aims to analyze the implementation of adolescent reproductive health services policy strategy and to identify factors affecting its implementation in Semarang regency. The method used in this research is qualitative descriptive. Data collection techniques used through in-depth interviews, observation, and literature review. This study refers to Government Regulation No. 61 of 2014 and uses Grindle's implementation model. The results showed that adolescent reproductive health services got less attention so that it has not been able to achieve the desired goals. It is due to the lack of good coordination between the involved implementers, implemented strategies are less effective, Semarang Regency Government has not yet prepared technical guidance on teenagers reproductive health service policy, and distribution of beneficiaries is not evenly distributed.